Gold Nanoparticles Supported on Mesoporous Titania Thin Films with High Loading as a CO Oxidation Catalyst. Issue 8 (28th March 2017) - Akita, Shingo; Amemiya, Makoto; Matsumoto, Takanori; Jikihara, Yohei; Nakayama, Tsuruo; Hossain, Md. Shahriar A.; Kani, Kenya; Ishii, Daisuke; Islam, Md. Tofazzal; Jiang, Xiangfen; Fatehmulla, Amanullah; Farooq, Wazirzada Aslam; et al.
Abstract: In the present work, 2.4 nm gold nanoparticles (Au NPs) are uniformly dispersed on mesoporous titania thin films which are structurally tuned by controlling the calcination temperature. The gold content of the catalyst is as high as 27.8 wt %. To our knowledge, such a high loading of Au NPs with good dispersity has not been reported until now. Furthermore, the reaction rate of the gold particles is enhanced by one order of magnitude when supported on mesoporous titania compared to non‐porous titania. This significant improvement can be explained by an increase in the diffusivity of the substrate due to the presence of mesopores, the resistance to agglomeration, and improved oxygen activation. Abstract : Clash of the Titania : In the present work, 2.4 nm gold nanoparticles (Au NPs) are uniformly dispersed on mesoporous titania thin films which are structurally tuned by controlling the calcination temperature. The gold content of the catalyst is as high as 27.8 wt %. Furthermore, the reaction rate of the gold particles is enhanced by one order of magnitude when supported on mesoporous titania compared to non‐porous titania.